How do atria affect navigation in multi-level museum environments?. (3rd September 2021) - Lazaridou, Athina; Psarra, Sophia
Abstract : How do people explore multiplex environments? What role do atria play in spatial navigation? These are critical questions for architectural design. However, few studies have examined the role atria play in visitors' exploration of museums. Consequently, the relationship between free exploration and the design of atria in museums is not well understood. A pilot study in the Ashmolean Museum indicated that atria influence navigation. The Museum, therefore, lends itself as a case study to assess the impact of visual connections upon exploration and orientation. We present an experimental study with two conditions: a highly-detailed realistic virtual model of the building and a modified virtual model of the same building, eliminating the views crossing through the atria. Two hypotheses are tested: first, that visitors' paths will be different depending on the amount of visual information they receive inside each experimental condition; second, that visitors' ease of exploring and viewing the environment will also differ. Analysis confirmed that participants followed different paths in the two experimental conditions. Users visiting the exact model turned their heads around fewer times than users visiting the modified model. These findings suggest that atria play a significant role in nudging movement and affect the ease of navigation.